Interactions of Self-Assembled Bletilla Striata Polysaccharide Nanoparticles with Bovine Serum Albumin and Biodistribution of Its Docetaxel-Loaded Nanoparticles - Guangyuan Zhang; Jin Qiao; Xin Liu; Yuran Liu; Ji Wu; Long Huang; Danyang Ji; Qingxiang Guan (Pharmaceutics)
Amphiphilic copolymers of stearic acid (SA)-modified Bletilla striata polysaccharides (BSPs-SA) with three different degrees of substitution (DSs) were synthesized. The effects of DS values on the properties of BSPs-SA nanoparticles were evaluated. Drug state, cytotoxicity, and histological studies were carried out. The affinity ability of bovine serum albumin (BSA) and the BSPs-SA nanoparticles was also characterized utilizing ultraviolet and fluorescence spectroscopy. Besides, the bioavailability and tissue distribution of docetaxel (DTX)-loaded BSPs-SA nanoparticles were also assessed. The results demonstrated that the DS increase of the hydrophobic stearic acid segment increased the negative charge, encapsulation efficiency, and drug-loading capacity while decreasing the critical aggregation concentration value as well as the release rate of docetaxel from the nanoparticles. Docetaxel was encapsulated in nanoparticles at the small molecules or had an amorphous status. The inhibitory capability of DTX-loaded BSPs-SA nanoparticles against 4T1 tumor cells was superior to that of Duopafei®. The ultraviolet and fluorescence results exhibited a strong binding affinity between BSPs-SA nanoparticles and bovine serum albumin, but the conformation of bovine serum albumin was not altered. Additionally, the area under the concentration–time curve (AUC0–∞) of DTX-loaded BSPs-SA nanoparticles was about 1.42-fold higher compared with Duopafei® in tumor-bearing mice. Docetaxel levels of DTX-loaded BSPs-SA nanoparticles in some organs changed, and more docetaxel accumulated in the liver, spleen, and the tumor compared with Duopafei®. The experimental results provided a theoretical guidance for further applications of BSPs-SA conjugates as nanocarriers for delivering anticancer drugs.